Human Resource Needs of Critical Units of Selected University Libraries in Ogun State, Nigeria: An Expository Analysis of the Outsourcing Option - Ajike, Florence Chidinma; Aina, Rachael Folashade (MiddleBelt Journal of Library and Information Science, 2014)
This paper investigatedthe human resource needs of critical units of selected university libraries in Ogun State. It conducts an analysis of outsourcing of library activities in the selected university libraries. A total of five key library personnel were interviewed for the purpose of this research. They included University Librarians and their Deputies. The main method used was case study,conducted in three university libraries in Ogun State; Federal University of Agriculture, Abeokuta (Federal University); OlabisiOnabanjo University, Ago-Iwoye (State University) and Babcock University, Ilisan-Remo (Private University). The study revealed that all the libraries studied outsourced mainly the acquisition units to vendors. Other parts of the library operations they variously outsourced included bindery, photocopy and ICT units. This is an indication that library outsourcing has not taken its ground in South-West Nigeria from the evidence available from the selected libraries especially, in the area of cataloguing. It is therefore recommended that, in a situation where we have scarce professionals, outsourcing some of the library activities may be the best option considering the benefits thereof.